An Analysis of Pbi UINSU Students’ Understanding Of Transitive and Complex-Transitive Verbs in Syntax - Laita, Rahma; Wulandari, Wulandari; Yulianti, Dwi; Ismahani, Siti (MUDABBIR Journal Research and Education Studies, 2025)
This study investigates PBI UINSU students’ understanding of transitive and complex-transitive verbs in syntactic analysis using a mixed-methods approach. The participants were seven students from the English Education Department at UIN Sumatera Utara who had completed a syntax course. Data were collected through a Google Form questionnaire consisting of seven knowledge-based multiple-choice items and five Likert-scale statements measuring students’ perceptions and confidence levels. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic analysis. The findings reveal that students demonstrate a strong understanding of basic transitive verb constructions, particularly simple S–V–O patterns and the obligatory role of direct objects. However, their performance on complex-transitive verb items was less consistent, especially in identifying object complements and recognizing verbs that function as complex-transitive. Perception data indicate that although students generally feel confident in their understanding, confusion between direct objects and object complements remains evident. The study concludes that while students possess adequate foundational knowledge of transitive verbs, greater instructional emphasis on functional analysis and object complements is necessary to enhance their syntactic competence in analyzing complex-transitive constructions